METHODS OF IMPROVING THE STUDY OF EQUATIONS AND SYSTEMS OF EQUATIONS IN GENERAL SECONDARY SCHOOLS AND ACADEMIC LYCEUMS (Web of Teachers: Inderscience Research, 2025)
This methodological manual is aimed at improving the teaching of equations and systems of equations in general secondary schools and academic lyceums. The manual contains theoretical and practical recommendations for teachers teaching mathematics. Basic concepts of equations and systems of equations and the stages of their study; Methodological methods that serve to develop students' logical and analytical thinking skills; Innovative approaches to teaching equations on the basis of pedagogical technologies and interdisciplinarity; recommendations for eliminating complications that arise in the course of the lesson. is an effective tool for strengthening knowledge, increasing interest in the subject, and developing skills for solving practical problems. The manual is intended for mathematics teachers, methodologists and scientific researchers.